Effects of 1-methylcyclopropene on postharvest quality of Roxo-de-Valinhos fresh ripe figs - Tofanelli, Mauro Brasil Dias; Cuquel, Francine Lorena; Medeiros, José Gilberto Sousa; D’angelo, Jessica Welinski de Oliveira (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2018)
The fig is one of the most perishable fruits during the postharvest phase, which has prompted studies to evaluate the effects of substances applied on figs after harvest in order to extend their postharvest life. The aim of this work was to evaluate the effects of different concentrations of 1-methylcyclopropene (1-MCP) on the postharvest quality of Roxo de Valinhos figs. The research was conducted by applying 4 concentrations of 1-MCP (0 - control, 5, 10, and 20 μg L-1) on figs, after which the fruits were evaluated at five different storage times (0, 4, 8, 12, and 16 days). The results showed that 20 μg L-1 of 1-MCP provided the best fruit firmness at day 12 after harvest. The 1-MCP treatments did not improve the total amount of total soluble solids (TSS), but we observed higher amount of total solids from 12 to 16 days of storage. Higher acidity was observed in the figs without a 1-MCP treatment at 8 days of storage and with 20 μg L-1 of 1-MCP after 12 days of storage. 1-MCP did not affect fruit weight loss. The figs treated with 1-MCP showed promising and rising values of firmness, acidity, and TSS at the highest dose. The TSS concentration tended to increase at the higher doses. As a result, it could be interesting to assay this substance with applications with higher concentrations than those used in the present study.